Molecular Study of Integrase Gene I and Integrase Gene II in Clinical Isolates of Pseudomonas aeruginosa - Zaki, Maysaa E. S.; Mahmoud, Noha M.; Rizk, Mohamed Anies (Infectious Disorders - Drug Targets, 2022)
Background: The presence of the class I integron gene is associated with the emergence of multiple drug resistance (MDR) phenotype in Pseudomonas aeruginosa (P. aeruginosa) isolates. Aim: The objectives of this research were to study the prevalence of integrase genes I (Intel I) and integrase genes II (Intel II) in clinical isolates of P. aeruginosa and its association with antibiotic resistance in these isolates. Methods: The study was a retrograde cross-sectional study that was carried out on 150 clinical isolates of P. aeruginosa isolated from patients with healthcare-associated infections. The isolates were subjected to biochemical identification and antibiotic sensitivity study by discs diffusion test. Intel I & Intel II genes were detected by polymerase chain reaction (PCR). Results: Intel I gene was present in 48% of the isolates, and Intel II was present in 1.3% of the isolates. Intel I gene was detected at a statistically significant high rate in MDR- P. aeruginosa (76.9%, P=0.001) compared to non-MDR- P. aeruginosa (3.4%), while intel II had a statistically insignificant increase in MDR- P. aeruginosa (1.1%, P=1.00) compared to non-MDR-P. aeruginosa (1.7%). Both Intl I/Intl II genes were detected in 2.2% of MDR-P. aeruginosa isolates and were absent in non- MDR-P. aeruginosa isolates with statistically insignificant difference (P=1.00). P. aeruginosa isolates with Intel I gene had an increase in antibiotic resistance pattern to the used antibiotics discs. However, this increase had statistically significant rates only for gentamicin (63.9%, P≤0.001), meropenem (47.2%, P=0.009), trimethoprim/sulfamethoxazole (37.5%, P=0.013) and imipenem (44.4%, P=0.025). Conclusion: The present study highlights the high prevalence of the Intel I gene in clinical isolates of P. aeruginosa, while the Intel II gene was less prevalent in these isolates. There was a significant association between the prevalence of the Intel I gene and the MDR phenotype of P. aeruginosa and resistance to gentamicin, meropenem, trimethoprim/sulfamethoxazole, and imipenem. These findings need future evaluation in a higher number of clinical isolates of P. aeruginosa.
Keywords: integrase I gene